2017
DOI: 10.1016/j.jcyt.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

An engineered biomarker system to monitor and modulate immune clearance of cell therapies

Abstract: Cell transplants offer a new opportunity to deliver therapies with novel and complex mechanisms of action. Understanding the pharmacology of cell transplants is important to deliver this new therapy effectively. Currently, however, there are limited techniques to easily track cells after intravenous administration due to the dispersion of the graft throughout the entire body. We herein developed an engineered cell system that secretes a luciferase enzyme to sensitively detect cell transplants independent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Biosensor cells were added to perfusate to circulate and engraft in liver, and fresh perfusate without cells was swapped in after 180 minutes to test for engraftment. gLuc has been used as a highly sensitive reporter for assessment of cells in vivo , so levels in the perfusate allow us to track its activity within the rat livers [18, 19, 21]. There was a consistent pattern of gLuc secretion: an initial buildup in the first three hours, then a drop at the time of switching to fresh perfusate, and resumption of increase during hours 4–6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosensor cells were added to perfusate to circulate and engraft in liver, and fresh perfusate without cells was swapped in after 180 minutes to test for engraftment. gLuc has been used as a highly sensitive reporter for assessment of cells in vivo , so levels in the perfusate allow us to track its activity within the rat livers [18, 19, 21]. There was a consistent pattern of gLuc secretion: an initial buildup in the first three hours, then a drop at the time of switching to fresh perfusate, and resumption of increase during hours 4–6.…”
Section: Resultsmentioning
confidence: 99%
“…The scope of this initial work was therefore to establish the integrity of biosensor cells infused into an organ using a constitutive CMV promoter to drive the secretion of Gaussia luciferase (gLuc), a bioluminescent biomarker probe [17]. We have previously investigated the pharmacokinetics of a cell therapy coupled with gLuc monitoring of cellular transplant [18] and used this technique to confirm immune clearance of such biomarker-secreting cells [19]. Furthermore, we tested the ability of a previously established ex vivo liver perfusion system [20] as a novel and enabling platform for engrafting cell biosensors into the organs prior to transplant.…”
Section: Introductionmentioning
confidence: 99%
“…The safety of the MSC administration was mainly assessed based on the influence on surgery and recovery after surgery. Although the clearance of systemically administered MSCs is within 24 hours both in animal models and humans (11), the differentiation of uncleared MSCs by the liver presents a significant risk in systemically administered MSCs. The patients in the study by Schweizer et al 2019 were not reported have any problems with MSC administration in 30 days.…”
Section: Safety Of Systemically Administered Bm-mscs In Prostate Cancersmentioning
confidence: 99%